2017
DOI: 10.1111/jvs.12565
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting understorey species responses to the canopy and root effects of a dominant shrub drive community composition

Abstract: Questions Contrasting understorey species responses to the effects of dominant species might occur within a single community even with neutral community‐level interactions. However, no studies have assessed the contribution of below‐ and above‐ground effects for all species of a community and their consequences for community composition. We tested the following hypotheses: (i) there are contrasting responses of understorey species to the canopy and root effects of a dominant shrub; (ii) the contrasting underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
4
13
1
Order By: Relevance
“…() and Wang et al. () in a similar system dominated by D. fruticosa . However, in our study, three species groups showed positive indirect effects from either the shrub's canopy or its roots, and only one showed negative indirect effects from the shrub's canopy.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…() and Wang et al. () in a similar system dominated by D. fruticosa . However, in our study, three species groups showed positive indirect effects from either the shrub's canopy or its roots, and only one showed negative indirect effects from the shrub's canopy.…”
Section: Discussionmentioning
confidence: 85%
“…Wang et al. () disentangled above‐ and below‐ground direct effects of Dasiphora using shrub removal and light reduction. They showed that these effects balanced each other, partially explaining the weak occurrence of direct net effects at the community level.…”
Section: Introductionmentioning
confidence: 99%
“…According to the “shifting limitations hypothesis” (see Gibson, 2009) the decline of positive interactions is expected in habitats with high density of large-sized benefactor, because of the intensifying competition (Kelemen et al, 2013; Macek et al, 2016; Goldberg et al, 2017). Intense belowground competition for nutrients and water is not expected in benign environment characterized by moist and fertile soil (Wilson and Tilman, 1991; Kiær et al, 2013); therefore, similarly to the decline of flowering success, competition for light can be responsible for the loss of species richness in the terminal part of the gradient (Lepš, 1999; Borer et al, 2014; Wang et al, 2017). Moreover, the accumulated litter and the allelopathic effect can also contribute to this phenomenon (Barkosky and Einhellig, 2003; Deák et al, 2011; Miglécz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The contrasting responses of species to neighbours observed within a single community have been shown to be related to species functional traits, in particular plant height, a good proxy of species' competitive ability for light (Díaz et al., 2016; Grime, 1974; Liancourt et al., 2005, 2009; Michalet et al., 2008; Wang, Michalet, et al., 2019), rather than traits related to growth rate such as leaf dry mass content (LDMC; Ackerly, 2004; Kunstler et al., 2016; Wright et al., 2004). Thus, it has been found that in species‐rich communities, particularly those from intermediate environmental conditions and characterized by high functional divergence, there are functionally different species, or group of species, with contrasting responses to their neighbours, which could balance the community‐level responses (Michalet et al., 2015; Wang et al., 2017). However, our knowledge is still limited on how changes in environmental conditions mimicking global change affect plant–plant interactions at both the species (including group of species) and community levels in communities living under intermediate stress conditions.…”
Section: Introductionmentioning
confidence: 99%